Hard carbon anodes of sodium-ion batteries: undervalued rate capability. Issue 17 (14th February 2017) - Li, Zhifei; Jian, Zelang; Wang, Xingfeng; Rodríguez-Pérez, Ismael A.; Bommier, Clement; Ji, Xiulei
Abstract : The intrinsic high rate capability of hard carbon anodes in sodium-ion batteries is revealed by a three-electrode cell. Abstract : The rate capability of hard carbon has long been underestimated in prior studies that used carbon/Na two-electrode half-cells. Through a three-electrode cell setup, we discover that it is the overpotential of the sodium counter electrode that drives the half-cells to the lower cutoff potential prematurely during hard carbon sodiation, particularly at high current rates, which prevents the hard carbon anode from being fully sodiated.